1992
DOI: 10.1002/bms.1200210506
|View full text |Cite
|
Sign up to set email alerts
|

Selective ion-molecule reactions of 2,5-dimethylpyrrole-γ-butyrolactone with dimethyl ether ions

Abstract: The llpe of bimolecuhr reactions as selective and sensitive diagnostic probes of analytically relevant molcules has undergone rapid development, especiPlly with tbe increasing availability of ion trapping techniques which allow detailed exsmiacrtioa of ion-molecule reactions. In this report, selective ion-molecule reactions of 2 , s dimethylpyrrole-y-butyrolacto~ with protoaated dimethyl ether and methoxymethylene cations (CH,OCH, +) are described. A qwdrupole ion trap and a triplequadrupole mass spectrometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…CAD-based MS n techniques have been applied to the characterization of unknown substances in many fields, including the pharmaceutical industry [19,20], and research on chemical warfare agents [21], proteins [22], volatile organic compounds [23], airborne oxidants [24], bacteria, DNA [25,26], and microextracted water samples [27]. Hydrogen/deuterium (H/D) exchange experiments [28][29][30] and molecular orbital calculations [31,32] have facilitated the differentiation of isomeric compounds.…”
Section: Introductionmentioning
confidence: 99%
“…CAD-based MS n techniques have been applied to the characterization of unknown substances in many fields, including the pharmaceutical industry [19,20], and research on chemical warfare agents [21], proteins [22], volatile organic compounds [23], airborne oxidants [24], bacteria, DNA [25,26], and microextracted water samples [27]. Hydrogen/deuterium (H/D) exchange experiments [28][29][30] and molecular orbital calculations [31,32] have facilitated the differentiation of isomeric compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sodium ion, chloride ion, silver ion or silicon ion participate in the formation of adduct ion in TOF-SIMS. Many papers (Donovan and Brodbelt 1992;Iida et al 1993;Wu et al 2001) have reported that adduct ions such as [M+13] + ion and [M+15] + ion, which are considered to be formed by methylene substitution and methyl-cation attachment, respectively, are generated in chemical ionization mass spectrometry such as electron spray ionization mass spectrometry. The m/z 301 ion generated from ferruginol by TOF-SIMS corresponds to [M+15] + ion, and is considered to be an adduct ion formed by methyl-cation attachment.…”
Section: Discussionmentioning
confidence: 99%
“…SIMR leading to the formation of methyne addition reactions in an ITMS has been investigated previously 6–9. Brodbelt and co‐workers examined methyne addition reactions by dimethyl ether (DME) CI for many compounds using an ITMS 10–26. The purpose of this paper is to describe the phenomenon when CAD is performed on the methyne adduct ions produced from both SIMR or CI, using both external and internal source ITMS instruments, where the SIMR can occur and lead to the formation of the protonated molecules or adduct ions.…”
Section: Introductionmentioning
confidence: 99%